Integrating IPR Integrity and Freedom of Expression: A Normative Analysis - Budi, V. Henry Soelistyo; Girodon-Hutagalung, Matahari; Irawati, Jovita (PROGRAM STUDI MAGISTER ILMU HUKUM FAKULTAS HUKUM UNIVERSITAS DIPONEGORO SEMARANG, 2024)
Algorithm as a digital innovation plays a crucial role in facilitating communication and public discourse. Its utilization is a significant issue that must be carefully analyzed to ensure it doesn’t impede key human rights, specifically the right to freedom of expression. The widespread use of digital platforms has created an urgency to examine this issue. The purpose of this study is to analyze the interaction between algorithms as digital innovations, their protection through the relevant IPR regimes, and their implications on freedom of expression. Through normative legal research methods and a statutory approach, this research finds that among various intellectual property regimes, the patent system offers the best potential for balancing the protection of algorithmic innovations with transparency. However, the analysis also reveals that current patent regulations still lack certain provisions to adequately safeguard freedom of expression in relation to patented algorithms. This research offers a proposed model of development that can be utilized to improve Indonesia’s protection of the right to freedom of expression through the patent regime, while also protecting algorithms as a key digital innovation.